Analisis Jumlah Kecelakaan Lalu Lintas, Korban, dan kerugian di Provinsi Lampung Tahun 2021 Dengan Metode K-Means Cluster - Rivai, Muklas; Hutabarat, Aulia Khairani; Halawa, Doni Hardian; Satrio, Ilham; Tarmizi, Muhammad Syauki; Frasiska, Nadia; Pratiwi, Niken; Alma, Zalikha (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Abstract: Provinsi Lampung is facing a serious challenge regarding the high rate of traffic accidents, triggered by the increasing number of vehicles and inadequate infrastructure. Low awareness of traffic regulations also serves as a major cause of accidents. This research employs the Cluster Analysis method within the Geographic Information System (GIS) to categorize traffic accident data in Lampung Province for the year 2021. The data encompasses the number of accidents, fatalities, serious injuries, minor injuries, and financial losses across 14 districts/cities. The cluster analysis results identify two main groups with distinct characteristics. The first cluster exhibits a low accident rate, while the second cluster shows a high accident rate, contributing significantly to the total number of accidents, fatalities, serious injuries, minor injuries, and financial losses. Recommendations for interventions are tailored to the characteristics of each cluster, emphasizing either fatal injury prevention or road infrastructure improvements. The findings of this research provide a foundation for designing more effective strategies to reduce accident risks and enhance traffic safety in Lampung Province Keywords: K-means, Accidents, Lampung Province